Validación de un método analítico para la cuantificación de naproxeno sódico en tableta de 550 mg mediante espectrofotometría ultravioleta - Murga Chávez, Schleimann Meffi (2012)
Analytical method validation is an integral part of quality control system, since that gives reliability of analytical results obtained in a laboratory, to ensure that a product meets established quality parameters. We present the validation of an analytical method for quantification of naproxen sodium 550 mg tablet using ultraviolet spectrophotometry, proposed by Josette Lean. The statistical parameters used in the study were chosen taking into account the type category proposed analytical method according to USP 32 which were: The linearity, which measures the ability of the analytical method to produce results that are proportional to the concentration of analyte This is demonstrated in the validation to obtain a correlation coefficient r = 0.999954, being the minimum permissible value of 0.999. The precision of the analytical method is the degree of consistency or of dispersion of test results. RSD values obtained from: 0814% to 90% concentration and 0092% to 110% concentration in repeatability, and 0.6586% to 90% concentration and concentration 1.0938% to 110% in reproducibility, we demonstrate the accuracy of the method analytical where the maximum value is RSD = 2.0% for repeatability and RSD = 3.0% for reproducibility. Accuracy measures the closeness of the results obtained by this method and the actual value. When applying for Student test to prove the correctness of the analytical method was obtained texp (0.586585) which is less than t tables (2.570582), so there is no significant difference between the mean recovery and the added amount of analyte, ie the percentage recovery of the analyte is close to 100% (99.86%). Selectivity determines the ability of the analytical method to measure the full content of sodium naproxen accurately and specifically in the presence of components that can be expected to be present, for example, impurities, degradation products and matrix components. In the analytical method this parameter is expressed as the deviation or the relative percentage error between the average value and the known value, yielding a percentage relative error of 1,680%, which is acceptable up to 2%, which is evidence that neither excipients, and the possible degradation products interfere with the determination of the substance, since it does not detect any significant response, thereby demonstrating the selectivity of the method.